San Cesario di Arles e i suoi continuatori e il monachesimo femminile - Degórski, Bazyli (Vox Patrum, 2016)
The article presents the Western Women Monasticism in Gaul spread by Saint Caesarius of Arles and his followers. In 506 Saint Caesarius of Arles undertook the building of the Women Monastery of Saint John, which was finalized in 512. The first Abbess of the monastery was Saint Caesarius’ sister, Saint Caesaria. Saint Caesarius wrote the Rule for the monastery in 534. After Saint Caesaria, another Caesaria became Abbess and the monastery counted up to 200 nuns in those years. To Abbess Caesaria, Saint Liliola and Rusticula succeeded. The influence of Saint Caesarius on Monasticism in Gaul was relevant, thought the Rule had a greater impact in Provence. The history of the monastery of Saint Andrew at Villeneuve, near Avinione, is not widely attested: one chronicle reports that, in 586, a woman named Caesaria died in the monastery. Even fewer historical sources concern other women monasteries in Gaul. According to tradition, also the monastery of Saint Peter du Puy in Orange was founded by Saint Caesarius. In the VI century the Rules of Saint Aurelianus of Arles, Regula ad monachos and Regula ad virgines were written as well. Saint Aurelianus of Arles founded two monasteries in Arles: a women monastery (Saint Mary’s) and a men monastery (Saints Peter and Paul’s).